Facile synthesis of porous CoAl-layered double hydroxide/graphene composite with enhanced capacitive performance for supercapacitors. (20th December 2015) - Zhang, Luojiang; Hui, Kwun Nam; Hui, Kwan San; Lee, Haiwon
Highlights: Porous graphene/CoAl-layered double hydroxide was obtained by gas-liquid interfacial method. The composite showed 3D structures with LDH uniformly grown on GNS surface. The unique structure led to an improved electrochemical performance. Graphical abstract: CoAl-LDH crystallites homogeneously grow on graphene sheets by a gas-liquid interfacial method and the composite exhibits improved electrochemical performance. Abstract: Many studies reported that layered double hydroxide/graphene composite showed significant aggregation, which limited their electrochemical performance for supercapacitor. Here, a porous highly-uniform CoAl-layered double hydroxide/graphene (G-LDH) composite was fabricated as a supercapacitor electrode material using a simple gas-liquid interfacial method. The results showed that the proposed gas-liquid interfacial method allowed morphological control of CoAl-LDH and reduced the stacking of CoAl-LDH lamellar crystallites on graphene, leading to a porous structure with a specific surface area of 98.2 m 2  g −1 and a pore volume of 0.42 cm 3  g −1 . The G-LDH sample achieved a specific capacitance of 479.2 F g −1 at 1 A g −1 and 341.2 F g −1 at 10 A g −1, which were much higher than those of the pure LDH sample fabricated by the gas-liquid interfacial method and the LDH/graphene sample synthesized by the conventional hydrothermal method. Moreover, the G-LDH composite exhibited long cycle stability with 93.9% of the specific capacitance (380.1 F g −1 ) retained at 3 A g −1 after 2000 cycles. This study provides a promising approach for the design and synthesis of porous layered double hydroxide/graphene composite with high capacitive performance, and can have potentially applications in energy storage.